Dexmedetomidine as an Adjuvant in Sciatic Nerve Block for Lower Limb Surgeries: An Observational Study - Krishna Prasad GV; Vipin Sharma Jaishree (Academia Anesthesiologica International, 2020)
Background: In recent anesthetic practice, peripheral nerve blocks (PNB) are used extensively for surgical anesthesia and non-surgical postop analgesia. PNBs offer many benefits over other anesthetic techniques in a certain population of patients and in some specific clinical setting that may contribute to faster and safer pain relief, increased patient satisfaction, reduced hospital stay, and decreased overall healthcare cost. However, the use of a single PNB is not sufficient enough to block the pain for longer durations. Hence, to prolong the effect of anesthesia without causing any adverse event, adjuvants are injected perineurally along with local anesthetic agents. Aim: The present study was aimed to evaluate the anesthetic efficacy of dexmedetomidine as an adjuvant in sciatic nerve block in lower limb surgery patients.Subjects and Methods:This observational non-randomized study involved 50 patients who were undergoing lower limb surgeries in the study period. The heart rate, blood pressure (both SBP and DBP), and peripheral oxygen saturation were recorded. A VAS score of more than 5 was considered significant and these patients received tramadol injection (75 mg) i.v. As rescue analgesia in the postop period. To prolong the effect of sciatic nerve block, dexmedetomidine (0.5 mcg/kg) was used.Results:In the maximum number of the patient,the complete block was achieved. Only 6 patients required tramadol injection as the rescue analgesia. No significant post and intraoperative complications were reported after the procedure.Conclusion:It is concluded from the study that the inclusion of dexmedetomidine (0.5 mcg/kg) in lower limb surgeries was associated with a prolonged duration of analgesia.